2016
DOI: 10.1142/s0192415x16500415
|View full text |Cite
|
Sign up to set email alerts
|

Timosaponin B-II Ameliorates Palmitate-Induced Insulin Resistance and Inflammation via IRS-1/PI3K/Akt and IKK/NF-κB Pathways

Abstract: This study aimed to investigate the effect of timosaponin B-II (TB-II) on palmitate (PA)-induced insulin resistance and inflammation in HepG2 cells, and probe the potential mechanisms. TB-II, a main ingredient of the traditional Chinese medicine Anemarrhena asphodeloides Bunge, notably ameliorated PA-induced insulin resistance and inflammation, and significantly improved cell viability, decreased PA-induced production of tumor necrosis factor-[Formula: see text] (TNF-[Formula: see text]) and interleukin-6 (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 41 publications
5
22
0
Order By: Relevance
“…In the current study, Sar remarkably reduced the albuminuria, kidney weight index, serum uric acid level, and the protein expression of FN and CoIV in kidney of STZ‐induced diabetic rats, suggesting that Sar may be the final contributor of the effects of steroidal saponins from AA. Timosaponin BII, BIII, AIII, and Sar have anti‐inflammatory effects by negative regulation of the NF‐κB pathways (J. Y. Kim et al, ; Lim et al, ; Yuan et al, ), and the vitro and in vivo anti‐inflammatory effects of Sar are more potent than its glycoside timosaponin AIII (Lim et al, ). The present study showed that Sar could suppress NLRP3 inflammasome activation in rat model of DN, as evidenced by the decreased levels of markers of inflammasome activation (elevated NLRP3, caspase 1 cleavage, and IL‐18 overproduction) in the kidney of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, Sar remarkably reduced the albuminuria, kidney weight index, serum uric acid level, and the protein expression of FN and CoIV in kidney of STZ‐induced diabetic rats, suggesting that Sar may be the final contributor of the effects of steroidal saponins from AA. Timosaponin BII, BIII, AIII, and Sar have anti‐inflammatory effects by negative regulation of the NF‐κB pathways (J. Y. Kim et al, ; Lim et al, ; Yuan et al, ), and the vitro and in vivo anti‐inflammatory effects of Sar are more potent than its glycoside timosaponin AIII (Lim et al, ). The present study showed that Sar could suppress NLRP3 inflammasome activation in rat model of DN, as evidenced by the decreased levels of markers of inflammasome activation (elevated NLRP3, caspase 1 cleavage, and IL‐18 overproduction) in the kidney of diabetic rats.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported to attenuate DN by reducing endoplasmic reticulum stress [28]. Similarly, A. asphodeloides Bunge was reported to reduce FG and improve impaired glucose tolerance in type 2 DM rats, and the flavonoids of A. asphodeloides Bunge are thought to reduce glucose and TGs [13]. Furthermore, TB-II, a main ingredient of A. asphodeloides Bunge, notably ameliorated IR and inflammation, and significantly improved cell viability decreased TNF-α and IL-6 levels, and the expression of p-NF-κBp65, p-IKKβ, p-IRS-1, p-PI3K, and p-Akt [13].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, A. asphodeloides Bunge was reported to reduce FG and improve impaired glucose tolerance in type 2 DM rats, and the flavonoids of A. asphodeloides Bunge are thought to reduce glucose and TGs [13]. Furthermore, TB-II, a main ingredient of A. asphodeloides Bunge, notably ameliorated IR and inflammation, and significantly improved cell viability decreased TNF-α and IL-6 levels, and the expression of p-NF-κBp65, p-IKKβ, p-IRS-1, p-PI3K, and p-Akt [13]. Coptis chinensis Franch was confirmed to significantly inhibit all the three periods of nonenzymatic protein glycation in vitro, including amadori products, dicarbonyl compounds, and AGEs formation [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The activated AKT can then activate or deactivate its myriad of substrates through its kinase activity. Recent studies have shown that the activation of the PI3K-AKT pathway reduces TNF-α production and suppresses inflammation [10,11]. Activation of the PI3K/AKT pathway limits JNK-mediated apoptosis by phosphorylating and inactivating ASK1 during the Enterovirus 71 (EV71) infection [12].…”
Section: Introductionmentioning
confidence: 99%